Improving Students Reading Skills Through Group Work in SMP Negeri 2 Tondano - Pilendatu, Noflin; Pelenkahu, Noldy; Liando, Nihta V. F (Program Studi Pendidikan Bahasa Inggris, 2025)
This study investigated the effectiveness of group work in improving students reading comprehension at SMP N 2 Tondano The research was motivated by the observation that many students struggled with reading English texts and demonstrated low comprehension abilities Using a pre experimental quantitative design the researcher administered a pre test and post test to a sample of the available 18 out of 30 seventh grade students due to their tardiness The intervention involved group work activities that aimed to foster collaboration and active participation during reading lessons Data were collected through multiple choice matching and completion tests and were analyzed for reliability and validity The findings showed a significant improvement in students reading comprehension after the implementation of group work as indicated by higher mean scores in the post test compared to the pre test Statistical analysis using a paired samples t test confirmed that this improvement was statistically significant The results suggested that group work was an effective strategy for enhancing reading skills among junior high school students However the study also found that some students continued to face challenges indicating the need for differentiated instruction and ongoing support Overall the research highlighted the value of collaborative learning in the English classroom and recommended the integration of group work strategies to improve reading comprehension < p>